Synthesized and Study the Structural and Morphological Properties of Polyaniline-Cadmium Sulfide Nanocomposite. - Rafic, Sewench N; Al-Jawad, Selma M. H; Muhsen, Mustafa M (Al-Nahrain Journal of Science, 2018)
The nanocrystalline CdS powder was prepared using sol–gel method. The polyaniline were prepared using chemical oxidative polymerization of aniline. The PANI-CdS nanocomposites had been prepared via same method of polyaniline preparation and different concentrations of CdS (10, 20, 30, 40 and 50 wt%) were added. X-ray diffraction shows that the peaks of emeraldine salt polyaniline powder are located at 2θ = 21.5o , 25.7o and 28.1o which indicate of polycrystalline polyaniline and the peaks of CdS powder are located at 2θ = 26.69, which is indicate of crystalline CdS coincides with hexagonal [002] structure, 2θ = 47.47 which is refers to CdS with hexagonal [103] and cubic [220] structures. The crystallite size of PANI and CdS were found to be 7.95 and 12.09 nm respectively. FTIR measurement indicates that there are interaction between polyaniline matrix and CdS nanoparticles. The AFM investigation shows that there is uniform istribution for CdS nanoparticles in the PANI matrix.